Characters In Tahfizh Islamic Boarding Schools In Banten Province - Abdul Rosyad; Zakaria Syafee'i; Naf'an Tarihoran (Institut Agama Islam An-Nawawi Purworejo, 2023)
Character education is an important agenda in education in Indonesia, this is because the problem of moral decadence has caused a downturn in various lines of life, therefore character education is considered the right solution to overcome it in order to form a civilized and good character generation. This study aims to determine how the application of character education in Pondok Pesantren Tahfidz Al-Uyun Lebak Banten Regency, Pesantren Darut Tahfidz Turus Pandeglang and Pondok Pesantren tahfidz Al-Ehsan Kampung Cihaseum Rt.04 Rw.06 Kelurahan, District, Pandeglang Regency. This research is descriptive qualitative research with field studies (field research) which aims to reveal facts, circumstances, variables and phenomena that occur. While the data is obtained based on observation (observation), interviews and document studies. The data analysis technique is the Miles and Huberman model which consists of; data collection, data reduction, data presentation and data verification. While the theory as a reference for character education is to use Sayyid Qutb's theory with the tawhid approach, or the concept of the oneness of God, being the main foundation in the concept of character education according to Qutb, as well as Thomas Lickona's theory which offers the concept of moral knowing, moral attitude (moral felling), and moral behavior (moral behavior). The results of the study found that the strategy used in the implementation of Sayyid Qutb and Thomas Lickona's theories at Pesantren Al-Uyun, Pesantren Darut Tahfidz Turus and Pondok Pesantren tahfidz Al-Ehsan is by integrating Islamic character values in learning in all subjects and through scheduled daily activities. While the methods used are methods; mentoring, exemplary, habituation, acculturation and discipline.